Pengaruh Ekstrak Tembakau sebagai Insektisida Botani terhadap Perkembangan Lalat Buah (Drosophila melanogaster) - Muhiddin Palennari; Hartati (Jurusan Biologi Universitas Negeri Makassar, 2009)
The important reason is that botanical insecticides didn’t cause environmental damage and not harmful to human health. As we know, tobacco leaf extract is one of many plant extract that use as botanical insecticides. It can kill fruit fly (Drossophyla melanogaster) that suck domestic plant. On the other hand tobacco leaves extract use as wound therapy also. Those effects are caused of the chemical compound such as alkaloid, saponyn, flavonoid and polyfenol.The objective of this study is to know the impact of tobacco leaf extract to development of D. melanogaster. Beside that, we observe the effective volume that causes optimal impact. Therefore we mix four type of tobacco leaf extract on D. melanogaster medium. In this case we apply 10 ml (P1), 20 ml (P2), 30 ml (P3) and 0 (P0). Then we observe the mortality. Further the mortality data is compiling by F analysis and LSD.The result shows that tobacco leaf extract caused negative impact to development of fruit fly on all stage of D. melanogaster (larvae, pupae, adult). The most effective impact seems on P3. Hopefully, the result of this study might useful to farmer that use botanical insecticide especially tobacco leaf user. So, user will have more advantages, because it didn’t harmful to human health and environmental.